Brief 51 20th Anniversary(1996 to 2015) of the Global Commercialization of Biotech crops and Biotech crop highlights in 2015 - James, Clive; Brookes, Graham; Iowa State University. Center for Agricultural and Rural Development (Phillippines: International service for the Acquisition of Agri-Biotech Applications (ISAAA), 2015)
Biotech crops have now been grown commercially on a substantial global scale since 1996. This paper examines the production effects of the technology and impacts on cereal and oilseed markets through the use of agricultural commodity models. It analyses the impacts on global production, consumption, trade and prices in the soybean, canola and corn sectors. The analysis suggests that world prices of corn, soybeans and canola would probably be, respectively, 5.8%, 9.6% and 3.8% higher, on average, than 2007 baseline levels if this technology was no longer available to farmers. Prices of key derivatives of soybeans (meal and oil) would also be between 5% and 9% higher, with rapeseed meal and oil prices being about 4% higher than baseline levels. World prices of related cereals and oilseeds would also be expected to be higher by 3% to 4%. The effect of no longer using the current widely used biotech traits in the corn, soybean and canola sectors would probably impact negatively on both the global supply and utilization of these crops, their derivatives and related markets for grain and oilseeds. The modelling [i.e., modeling] suggests that average global yields would fall for corn, soybeans and canola and despite some likely "compensating" additional plantings of these three crops, there would be a net fall in global production of the three crops of 14 million tonnes. Global trade and consumption of these crops/derivatives would also be expected to fall. The production and consumption of other grains such as wheat, barley and sorghum and oilseeds, notably sunflower, would also be affected. Overall, net production of grains and oilseeds (and derivatives) would fall by 17.7 million tonnes and global consumption would fall by 15.4 million tonnes. The cost of consumption would also increase by $20 billion (3.6%) relative to the total cost of consumption of the (higher) biotech-inclusive level of world consumption. The impacts identified in this analysis are, however, probably conservative, reflecting the limitations of the methodology used. In particular, the limited research conducted to date into the impact of the cost-reducing effect of biotechnology (notably in herbicide-tolerant soybeans) on prices suggests that the price effects identified in this paper represent only part of the total price impact of the technology.
"January 2010."
Keywords: biotechnology, cereals, crop yields, oilseeds, price effects, productivity.
Includes bibliographical references (p. 19).
Also available on the Internet.
Keywords: Plant biotechnology -- Economic aspects; Crops -- Prices